Phosphorylation of ovalbumin after pulsed electric fields pretreatment: Effects on conformation and immunoglobulin G/immunoglobulin E-binding ability - Yang, Wenhua; Duan, Wenjing; Li, Qiuhong; Duan, Dengle; Wang, Qin (Frontiers in Nutrition, 2022)
Ovalbumin (OVA) is one of major allergens of hen egg white with excellent nutritional and processing properties. Previous research exhibits that pulsed electric field (PEF) treatment could partially unfold OVA. This may contribute to the improvement of OVA phosphorylation. In this study, the effect of PEF pretreatment combined with phosphorylation on the structure and immunoglobulin (Ig) G/IgE-binding ability of OVA was investigated. The structural changes were measured by circular dichroism (CD), ultraviolet absorption, and fluorescence spectroscopy. The IgG- and IgE-binding abilities were determined by inhibition enzyme-linked immunosorbent assay (ELISA) using rabbit polyclonal antibodies and egg-allergy patients’ sera, respectively. The results showed that PEF pretreatment combined with phosphorylation markedly reduced the IgG- and IgE-binding abilities. It was attributed to the changes in secondary and tertiary structure, which was reflected in the increase of ultraviolet (UV) absorbance, α-helix content, and the increase the molecular weight. Moreover, it suggested PEF pretreatment improved the phosphorylation of OVA and enhanced the reduction of IgG/IgE-binding capacity of phosphorylated OVA. Therefore, PEF pretreatment combined with phosphorylation has the potential for developing a method for OVA desensitization.